RobotX: development of surface vehicle's awareness system about position and orientation in real-time - Mutaalim, Dihan Jannatan (Nanyang Technological University, 2023)
The Unmanned Surface Vessels (USV)s find widespread applications in military, commercial sectors and research, offering autonomous solutions associated with marine operations ranging from transportation to complex missions. In this project, the USV are utilised for the Maritime RobotX Challenge, which is a biannual competition held at the university level to challenge the students to design a USV that will be evaluated by performing various tasks. In order to navigate fully autonomously, it is important to develop the position and orientation awareness system of the USV, which is aided by GPS (Global Positioning System). This project aims to enhance navigation capabilities by focusing on implementing robust system software to provide a real-time awareness system of position and orientation. This paper begins by introducing the project’s motivation, and review from other teams’. Following that, the hardware selection and software development are proposed, including Robotics Operating System (ROS) implementation and Graphical User Interface (GUI) development. Next, the testing to compare the solution between the two proposed methods, including the detailed configuration, data collection, results and discussion are explained. This project implementation is expected to enhance the USV's overall performance in navigation system and contribute valuable insights to the future development of our USV.